“Estatuomanía” in Latin America. Approaches to the commemorative sculpture of the late 19th and early 20th centuries - Vanegas Carrasco, Carolina (2021)
A series of works from different cities in Latin America guide a reflection on the processes of creation, uses and practices around the memorial sculpture at its peak: the end of the nineteenth century and the beginning of the twentieth century. The comparative view aims to show some synchronies and asynchronies of these processes, as well as to propose a series of problems and authors to consider in the study of the commemorative sculpture of the region.